Solitary nodule of the lung: Analysis of 100 cases submitted to exploratory thoracotomy and anatomo-pathological control - Delgado, Bolívar; Brandolino, Héctor; Díaz, B (Cirugía del Uruguay, 1972)
The authors have undertaken a study of 100 cases of single lung nodes treated by thoracotomy and anatomopathological control; their findings are compared ·with those of other authors. Stress is laid on their site and on the predóminance, in this series, of hydatid cysts or their sequella ( 53 % ) . As a result of this study it appears that the. best ¡method of diagnosis is exploratory thoracotomy, which ,has low risk (1 %') and should consequently be em; ployed without delay. Cancer incidence is high in this type of lesion ( 44 % ). especially in patients over 50 years of age, and resection at this stage is the procedure which affords greater possibility of longterm survival.